GAMBARAN MOTORIK HALUS PADA ANAK TUNAGRAHITA DI SDN PURWOREJO II (SDLB) KOTA PASURUAN - Nur So’emah, Eka (JURNAL KEPERAWATAN SEHAT, 2016)
Children with mentally disability learn more slowly than a typical child. This can influence the fine motor skill because their IQ and their hand and eyes movement are below the average which therefore they have lower ability to do small movements. This case can influence their activities such writing, crumpling, holding, drawing, and other daily activities. This study is aimed to describe the fine motor skill of mentally disabled children in SDN Purworejo II (SDLB) Kota Pasuruan. This study uses descriptive design. The population is all 60 children with mentally disabled in the Total sampling. The instrument used is observation. The finding of the study showed that there were 53.3% of the respondents or equal to 32 children had fine motor skill with minimum help. It could be influenced by two factors those were age and sex. Parents have to aware the importance of helping their children practice the fine motor skill by joining socialization and reading related books.Keywords: Fine motor skills, Mentally Disabled